Left bundle branch pacing compared to left ventricular septal myocardial pacing increases interventricular dyssynchrony but accelerates left ventricular lateral wall depolarization - Curila, Karol; Jurak, Pavel; Jastrzebski, Marek; Prinzen, Frits; Waldauf, Petr; Halamek, Josef; Vernooy, Kevin; Smisek, Radovan; Karch, Jakub; Plesinger, Filip; Moskal, Pawel; Susankova, Marketa; et al. (Heart rhythm, 2021)
BACKGROUND: Nonselective His-bundle pacing (nsHBp), nonselective left bundle branch pacing (nsLBBp), and left ventricular septal myocardial pacing (LVSP) are recognized as physiological pacing techniques. OBJECTIVE: The purpose of this study was to compare differences in ventricular depolarization between these techniques using ultra-high-frequency electrocardiography (UHF-ECG). METHODS: In patients with bradycardia, nsHBp, nsLBBp (confirmed concomitant left bundle branch [LBB] and myocardial capture), and LVSP (pacing in left ventricular [LV] septal position without proven LBB capture) were performed. Timings of ventricular activations in precordial leads were displayed using UHF-ECG, and electrical dyssynchrony (e-DYS) was calculated as the difference between the first and last activation. Duration of local depolarization (Vd) was determined as width of the UHF-QRS complex at 50% of its amplitude. RESULTS: In 68 patients, data were collected during nsLBBp (35), LVSP (96), and nsHBp (55). nsLBBp resulted in larger e-DYS than did LVSP and nsHBp [- 24 ms (-28;-19) vs -12 ms (-16;-9) vs 10 ms (7;14), respectively; P <.001]. nsLBBp produced similar values of Vd in leads V5-V8 (36-43 ms vs 38-43 ms; P = NS in all leads) but longer Vd in leads V1-V4 (47-59 ms vs 41-44 ms; P <.05) as nsHBp. LVSP caused prolonged Vd in leads V1-V8 compared to nsHBp and longer Vd in leads V5-V8 compared to nsLBBp (44-51 ms vs 36-43 ms; P <.05) regardless of R-wave peak time in lead V5 or QRS morphology in lead V1 present during LVSP. CONCLUSION: nslbbp preserves physiological LV depolarization but increases interventricular electrical dyssynchrony. LV lateral wall depolarization during LVSP is prolonged, but interventricular synchrony is preserved.
Keywords: srdeční komory; Electrocardiography; Cardiac Pacing, Artificial; Ventricular Function, Left; Male; funkce levé komory srdeční; kardiostimulace umělá; Ventricular Septum; následné studie; Aged; Prospective Studies; mužské pohlaví; senioři; Follow-Up Studies; Depolarization duration; Ultra-high-frequency electrocardiography; lidé; blokáda Tawarova raménka; ženské pohlaví; Humans; Left bundle branch pacing; Dyssynchrony; Left ventricular septal myocardial pacing; Bundle of His; Bundle-Branch Block; His-bundle pacing; Heart Ventricles; Female; Hisův svazek; mezikomorová přepážka; elektrokardiografie; prospektivní studie